Comparative Effectiveness of Adjuvant Treatment for Resected Hepatocellular Carcinoma: A Systematic Review and Network Meta-Analysis - Liu, Ying; Wang, Yuzhu; Guo, Xinkun; He, Yifeng; Zhou, Jian; Lv, Qianzhou; Huang, Xiaowu; Li, Xiaoyu (Frontiers in Oncology, 2021)
Background: It is controversial whether adjuvant treatment could be recommended for hepatocellular carcinoma (HCC) after curative hepatectomy. Thus, we performed a network meta-analysis (NMA) to assess adjuvant treatment’s benefit and determine the optimal adjuvant regimen. Methods: We systematically searched PubMed, Embase and Cochrane Library for randomized controlled trials comparing adjuvant therapy versus no active treatment after curative hepatectomy among patients with HCC. Pooled data on recurrence and overall survival (OS) were analyzed within pairwise meta-analysis and NMA. Results: Twenty-three eligible trials (3940 patients) reporting eight treatments were included. The direct meta-analysis showed that adjuvant therapy prevented the recurrence (OR = 0.65; 95% CI: 0.55, 0.77; P = 0.177; I2 = 21.7%) and contributed to OS (HR = 0.63; 95% CI: 0.54, 0.73; P = 0.087; I2 = 31.1%) in comparison to the observation. In the NMA, internal radiotherapy (IRT; OR = 0.55; 95% CI: 0.39, 0.77; SUCRA = 87.7%) followed by hepatic artery infusion chemotherapy (HAIC; OR = 0.6; 95% CI: 0.36, 0.97; SUCRA = 77.8%), and HAIC (HR = 0.44; 95% CI: 0.21, 0.87; SUCRA = 82.6%) followed by IRT (HR 0.54; 95% CI:0.36, 0.81; SUCRA = 69.7%) were ranked superior to other treatments in terms of preventing recurrence and providing survival benefit, respectively. Conclusions: The addition of adjuvant therapy lowers the risk of recurrence and provide survival benefit after surgical resection for HCC. HAIC and IRT are likely to be the two most effective adjuvant regimens.